Cerebral blood flow is lower in youth with type 2 diabetes compared to obese controls: A pilot study. Issue 3 (17th January 2022) - Redel, Jacob M.; DiFrancesco, Mark; Lee, Gregory R.; Ziv, Adi; Dolan, Lawrence M.; Brady, Cassandra C.; Shah, Amy S.
Abstract: Aim: The cerebral vasculature may be susceptible to the adverse effects of type 2 diabetes. In this pilot study, we compared cerebral blood flow (CBF) in youth with type 2 diabetes to obese, euglycemic controls, and explored the association between CBF and a non‐invasive measure of atherosclerosis, carotid intima‐medial thickness (IMT). Methods: Global and regional CBF were compared between youth with type 2 diabetes (mean age 16.7 ± 2.0 years, n = 20) and age, race, and sex similar obese youth without diabetes (17.4 ± 1.9 years, n = 19) using arterial spin labeling magnetic resonance imaging. Mean CBF values were compared between groups. Voxel‐wise results were evaluated for statistical significance ( p < 0.05) after adjustment for multiple comparisons. Carotid IMT in the type 2 diabetes group was correlated with CBF. Results: Compared to obese controls, the type 2 diabetes group had significantly lower global CBF (49.7 ± 7.2 vs. 63.8 ± 11.5 ml/gm/min, p < 0.001). Significantly lower CBF was observed in multiple brain regions for the type 2 diabetes group, while no regions with higher CBF were identified. In the type 2 diabetes group, carotid IMT was inversely correlated with CBF, both globally (r = −0.70, p = 0.002) and in regional clusters. Conclusions: In this pilot study, lower CBF was seen in youth with type 2 diabetes compared to youth with obesity and IMT was inversely correlated with CBF. Cerebrovascular impairment may be present in youth with type 2 diabetes. These findings could represent a mechanistic link to explain previously reported brain volume and neurocognitive differences.